Adaptation and validation of the children’s cognitive triad inventory for Indonesian students - Ktut Dianovinina; Endang Retno Surjaningrum; Primatia Yogi Wulandari (Institute of Advanced Engineering and Science, 2024)
Depression causes student learning problems. Depressive symptoms are influenced by automatic thoughts that contain a negative cognitive triad. A valid and reliable instrument to measure the cognitive triad in adolescents is essential to identify one of the risk factors for depressive disorders in adolescents. At the same time, Indonesia has no instrument to measure this. This study aims to adapt the children’s cognitive triad inventory (CTI-C) into an Indonesian version and to examine its psychometric properties. Data were collected from 1,184 students aged 13-19 (mean=15.32, SD=1.62) using the 36-item CTI-C. The CTI-C instrument adaptation process refers to the international test commission (ITC). The results of confirmatory factor analysis (CFA) showed comparative fit index (CFI)=0.95, Tucker-Lewis’s index (TLI)=0.94, root mean square error of approximation (RMSEA)=0.071, standardized root mean square residual (SRMR)=0.056, and goodness of fit index (GFI)=0.82, with a load factor range of 0.43-0.80 for the view of self, 0.43-0.68 for the view of the world, and 0.37-0.70 for the view of the future. The Cronbach’s alpha coefficient ranged from 0.81 to 0.84 for the subscales and 0.93 for the total score. Thus, the Indonesian version of the CTI-C can measure the cognitive triad in Indonesian students aged 13-19.